Research into dedifferentiation during epimorphic regeneration in Xenopus and Zebrafish - Rodrigues, Alexandre Miguel Cavaco, 1983- (2013)
Tese de doutoramento, Ciências Biomédicas (Ciências Morfológicas), Universidade de Lisboa, Faculdade de Medicina, 2013